Faith-based organisation and social development : the case of Markazosshabab Al-Muslim Fil Filibbin in Lanao Del Sur - Nadhera Mohammad Qassem (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This study investigates the contribution of faith-based organisations in social development with special reference to Markazosshabab al-Muslim fil Filibbin. It is geared towards finding out the factors that led to the formation of Markazosshabab al Muslim fil Filibbin in the Philippines and its values and principles upon which it was established. This study serves as a contribution to the study of faith-based organisations and social development and the role of democracy in this. Furthermore, it hopes to find out how these values and principles, upon which Markazosshabab is established, shape its outlook and define the type of developmental activities and programmes it pursues in the Philippines. Then, the implementation of these developmental activities is addressed. It is also equally important to figure out the nature of the relationship between the Markazosshabab and the Philippine government. This research has mainly administered interviews as the main source of data complemented by documents, theses, magazines and reports and a thematic analysis was used to analyse the data. The findings of this study reveal that the main factor that led to the formation of the Markazosshabab was a religious one. It is Islam that triggered the foundation of this organisation. Markazosshabab was founded on Islamic tenets in which its guiding principles are evident in its organisational objectives and mission. By that, all of its programmes and activities are based upon these objectives rooted in Islamic values and principles. However, this organisational sphere of influence is limited. Though it has spread to other places in the Philippines, its main area of concentration is the Meranao people. This is due to some factors and challenges it faces in implementing and widening its activities and programmes. Also, it is found out through this study that there is an existing relationship between the Markazosshabab and the Philippine government and this is in the form of cooperation and coordination. The findings of this study further reveal that the existence of Islamic organisations such as the Markazosshabab, is allowed because of the democratic system of government and the objectives of Markazosshabab that support governmental programmes. Indeed, faith-based groups such as Markazosshabab is a potential partner of the Philippine government in realising social development. Lastly, this study would like to propose a future study that is built on the same assumptions and to conduct additional research which include other stakeholders of this organisation since this study is limited to executive members only.